2003
DOI: 10.1051/apido:2003010
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization between European and African-derived honeybee populations (Apis mellifera) at different altitudes in Per�

Abstract: -The current status of admixture between Apis mellifera of African and European origin was studied in populations from different altitudinal regions of Perú. Worker bees from 7 altitudinal regions were analysed by morphometrics and mtDNA RFLPs. Our results showed that the rates of admixture between African-derived and resident European populations have depended on the altitude of the region. Our finding of hybrid colonies at elevations above 2 500 m supports the hypothesis that climate alone may not restrain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Selection rather than competitive displacement seems a more plausible hypothesis for the genetic composition of Mexican bees. Selection would favor genes advantageous to survival in tropical or temperate climate (Moritz and Meusel 1992;Quezada-Euán et al 2003) which is in agreement to our findings of Africanized-derived markers more frequent in tropical regions and European-derived markers more frequent in temperate regions. Concomitantly, a gradient of Africanization seems to exist with higher frequencies of Africanized colonies in the Mexican tropical regions and lower in the temperate ones, similar to those found in the southern neotropics (Sheppard et al 1991;Quezada-Euán et al 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Selection rather than competitive displacement seems a more plausible hypothesis for the genetic composition of Mexican bees. Selection would favor genes advantageous to survival in tropical or temperate climate (Moritz and Meusel 1992;Quezada-Euán et al 2003) which is in agreement to our findings of Africanized-derived markers more frequent in tropical regions and European-derived markers more frequent in temperate regions. Concomitantly, a gradient of Africanization seems to exist with higher frequencies of Africanized colonies in the Mexican tropical regions and lower in the temperate ones, similar to those found in the southern neotropics (Sheppard et al 1991;Quezada-Euán et al 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Climate is probably the main abiotic factor determining the distribution of Africanized bees in the Americas (Sheppard et al 1991;Hall and McMichael 1992;Quezada-Euán et al 2003). Mexico is a climate-diverse country, and accordingly, there are five recognized beekeeping regions, namely the following: North, Central highlands, Pacific coast, Gulf coast, and the Yucatan Peninsula (Labougle 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The climatic conditions in desert zones could also be less suitable for Africanized feral colonies, especially at night when environmental temperatures may fall below 0 • C. However, AHB have been found at high altitudes where cold conditions are extreme (Quezada-Euán et al, 2003). Therefore we suggest that nest availability may be the main factor reducing the numbers of feral colonies.…”
Section: Discussionmentioning
confidence: 82%
“…One of the main problems in elucidating the relative importance of different factors and the mechanisms involved in the process is the lack of long term detailed studies before, during and after the arrival of colonizing swarms (QuezadaEuán, 2000; Pinto et al, 2005). The study of the expansion and establishment of AHBs in NW Mexico can provide additional information to test hypothesis regarding the relative effect of the size of the resident EHB population and that of climatic and geographic barriers (Quezada-Euán et al, 2003) different from the ones that AHBs have encountered during their expansion history across tropical and subtropical Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…The few previous studies confirmed the admixture of European and African-lineages in Peruvian honey bees due to introgression of African genes into the previously European dominated honey bee populations (PerezCastro E E, et al, 2002;Quezada-Euan J J G, et al, 2003) as in other Neotropical countries (Smith D R, et al, 1989). Other studies focused on the control of the ectoparasitic mite Varroa destructor (Dávila M, et al, 1987;Tejada G, 1995).…”
mentioning
confidence: 82%